1995
DOI: 10.2307/1369178
|View full text |Cite
|
Sign up to set email alerts
|

Nest-Site Relationships among Cavity-Nesting Birds of Riparian and Snowpocket Aspen Woodlands in the Northwestern Great Basin

Abstract: We examined nest-site and nest-cavity characteristics for six species of cavitynesting birds in montane riparian and snowpocket aspen (Populus tremuloides) woodlan& in the northwestern Great Basin. Live trees and snags with DBH >24 cm were favored as nest sites by all species. Red-naped Sapsuckers (Sphy;apicus nuchalis) and Northern Flickers (Colaptes auratus) provided different sizes ofnest cavities for a suite of nonexcavator species. Flickers preferentially nested in snags; sapsuckers nested primarily in li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(85 citation statements)
references
References 38 publications
4
80
0
1
Order By: Relevance
“…In addition, cavity-nesting birds employ exclusionary strategy of territorialism (Wesolowski 1989). For instance, Starlings (Sturnus vulgaris) are known to constrain Tree Swallows (Tachycineta bicolour) to smaller nest sizes and remote nest sites from woodlands (Dobkin et al 1995). In another example, woodhoopoes defend their core territorial areas where suitable cavities for roosting and breeding are found from competitor species (Du Plessis 1992;Du Plessis, Simmons & Radford 2007).…”
Section: Conservation Implicationsmentioning
confidence: 99%
“…In addition, cavity-nesting birds employ exclusionary strategy of territorialism (Wesolowski 1989). For instance, Starlings (Sturnus vulgaris) are known to constrain Tree Swallows (Tachycineta bicolour) to smaller nest sizes and remote nest sites from woodlands (Dobkin et al 1995). In another example, woodhoopoes defend their core territorial areas where suitable cavities for roosting and breeding are found from competitor species (Du Plessis 1992;Du Plessis, Simmons & Radford 2007).…”
Section: Conservation Implicationsmentioning
confidence: 99%
“…In the United States, the nest niche of the introduced European Starling and House Sparrow Passer domesticus overlapped with native Bluebirds Sialia spp., and caused great decline of their populations (Erskine & McLaren 1976, Sedgwick 1997. The competition with the Starling also limited the Tree Swallow Tachycineta bicolor to smaller holes and nest sites farther from woodland edges (Rendell & Robertson 1989, Dobkin et al 1995. The aggressiveness of the Starling could exert selection on other species to shift their nesting phenology and behaviour (Koenig 2003).…”
Section: Niche Overlap and Role Of Competitionmentioning
confidence: 99%
“…In upper midwestern oak forests, secondary cavity-dwelling wildlife like the Great-crested Flycatcher, Tufted Titmouse (Baeolophus bicolor), House Wren (Troglodytes aedon), White-breasted Nuthatch, Barred Owl, and Southern Flying Squirrel (Glaucomys volans) all use old woodpecker holes for nesting. Studies have shown that lack of suitable nest sites is a limiting factor for many species of cavity-nesting birds (Cunningham et al 1980;Zarnowitz and Manuwal 1985;Dobkin et al 1995).…”
Section: Management Implicationsmentioning
confidence: 99%
“…Research on woodpecker nest site selection in the western United States is most extensive (McClelland and Frissel 1975;Bull and Meslow 1977;Scott 1978;Scott et al 1978;Mannan et al 1980;Scott et al 1980;Scott and Oldemeyer 1983;Winternitz and Cahn 1983;Raphael and White 1984;Zarnowitz and Manuwal 1985;Sedgewick andKnopf 1986, 1990;Li and Martin 1991;Schreiber and deCalesta 1992;Dobkin et al 1995).…”
mentioning
confidence: 99%